In vitro and in vivo activity of a novel locked nucleic acid (LNA)-inhibitor-miR-221 against multiple myeloma cells. - Maria Teresa Di Martino; Annamaria Gullà; Maria Eugenia Gallo Cantafio; Emanuela Altomare; Nicola Amodio; Emanuela Leone; Eugenio Morelli; Santo Giovanni Lio; Daniele Caracciolo; Marco Rossi; Niels M Frandsen; Pierosandro Tagliaferri; et al. (PLoS ONE)
Background & aim The miR-221/222 cluster is upregulated in malignant plasma cells from multiple myeloma (MM) patients harboring the t(4;14) translocation. We previously reported that silencing of miR-221/222 by an antisense oligonucleotide induces anti-MM activity and upregulates canonical miR-221/222 targets. The in vivo anti-tumor activity occurred when miR-221/222 inhibitors were delivered directly into MM xenografts. The aim of the present study was to evaluate the anti-MM activity of a novel phosphorothioate modified backbone 13-mer locked nucleic acid (LNA)-Inhibitor-miR-221 (LNA-i-miR-221) specifically designed for systemic delivery. Methods In vitro anti-MM activity of LNA-i-miR-221 was evaluated by cell proliferation and BrdU uptake assays. In vivo studies were performed with non-obese diabetic/severe combined immunodeficient (NOD.SCID) mice bearing t(4;14) MM xenografts, which were intraperitoneally or intravenously treated with naked LNA-i-miR-221. RNA extracts from retrieved tumors were analyzed for miR-221 levels and modulation of canonical targets expression. H&E staining and immunohistochemistry were performed on retrieved tumors and mouse vital organs. Results In vitro, LNA-i-miR-221 exerted strong antagonistic activity against miR-221 and induced upregulation of the endogenous target p27Kip1. It had a marked anti-proliferative effect on t(4;14)-translocated MM cells but not on MM cells not carrying the translocation and not overexpressing miR-221. In vivo, systemic treatment with LNA-i-miR-221 triggered significant anti-tumor activity against t(4;14) MM xenografts; it also induced miR-221 downregulation, upregulated p27Kip1 and reduced Ki-67. No behavioral changes or organ-related toxicity were observed in mice as a consequence of treatments. Conclusions LNA-i-miR-221 is a highly stable, effective agent against t(4;14) MM cells, and is suitable for systemic use. These data provide the rationale for the clinical development of LNA-i-miR-221 for the treatment of MM.